Student nurses' knowledge, attitudes and practices towards the management of burn injuries at an institution of higher learning in Windhoek, Namibia - Mukondeli, Sofia; Amakali-Nauiseb, Taimi; Emvula, Olivia (International Journal Of Community Medicine And Public Health, 2025)
Background: Health facilities in Windhoek, Namibia are equipped with almost all the equipment’s needed for managing burn injury patients. However, there is still a death rate of 5.43 per 100 000 patients admitted with burn injuries. Methods: A cross -sectional descriptive study design with quantitative approaches was utilized, a structured questionnaire was completed. Results: The respondents, results show that 84.7% (n=61) believe any of the registered nurses, enrolled nurse or doctor who was available can attend to burn patients first. In addition, 57.6% (n=41) wound not dress burn wounds aseptically, 68% (n=49) of the respondents would regard attending to burn injury patient as an emergency. 58.3% (n=42) would cover burn wounds with paraffin gauze. 63.9% (n=46) believe only flamazine should be applied on burn wound. 72.2% (n=52) believed one can offer burn patients with food and fluids and let them lie on the back. 63.9% (n=46) believed one cannot initiate a patient on oxygen if they reach 90% on room air, 90.3% believed they can irrigate burn wounds with water resulting from chemical burns with corrosive materials immediately. Furthermore, 56.9% (n=41) would not place a blood pressure cuff on the severely burn patient, however 43.1% (n=31) would place a blood pressure cuff on a severely burned patient. Conclusions: It is important for both the institution of higher learning, student nurses, and stakeholders to intervene and promote the consistent knowledge attitudes and practices to enable students to manage burn injuries.